PRAWNO-ADMINISTRACYJNE DETERMINANTY FUNKCJONOWANIA RADIOFONII I TELEWIZJI W POLSCE - Mrozek, Jacek Janusz (Civitas et Lex, 2018)
This article is an attempt at defining legal and administrative determinants of broadcasting in Poland. The author has undertaken an analysis of the statutory tasks and system of broadcasting companies, including their executive (management boards), supervisory (supervisory boards) and advisory and consultative bodies (programme boards). He also provides details concerning the statutory requirements for the appointment and dismissal of the National Broadcasting Council and its principles of operation and rulemaking, with particular reference to several dozen regulations governing the media market in Poland.